Judicial Practice in Distribution of Inheritance (miÌ„raÌ„th) in Islamic Courts in Nigeria - Ismael, Ismael Saka; Oba, Abdulmumini Adebayo (De Jure: Jurnal Hukum dan Syari'ah, 2019)
Inheritance is one of the issues that has attracted the attention of many Islamic jurists. Although it has been regulated in fiqh books, the distribution of inheritance has the potential to cause disputes. This paper examines the legal framework governing distribution of inheritance under Islamic law as interpreted in Islamic courts in Nigeria. The paper analyses decided cases in constructing the judicial practice in distribution of estates among heirs in Islamic courts in Nigeria from commencement to conclusion of such distributions. This research is a legal normative study using judicial case and conceptual approaches. The paper concludes that Islamic courts in Nigeria adhere strictly to the Maliki school in the matters concerning distribution of inheritance.